Quantification of nitrate fluxes to groundwater and rivers from different land use types - Diadin, Dmytro; Vystavna, Yuliya; Vergeles, Yuri (Hungarian Geographical Bulletin, 2018)
Nitrate enters aquatic systems from anthropogenic and natural sources affecting drinking water supply and surface water eutrophication. Conventional hydro-chemical measurements have been used together with the geographic information system (GIS) and stable isotopes techniques to track nitrate origin, sources distribution and quantify their fluxes from various land use types to ground and surface waters in East Ukraine. Average fluxes of nitrate in groundwater are estimated at 356 kg year-1 km-2 from settlements (mostly rural), 214 kg year-1 km-2 – from agricultural lands and 73 kg year-1 km-2 – from forested areas. According to the mass balance estimation, nitrogen input (150 kg year-1 km-2) occurs mainly in the upper part of the Seversky Donets River basin and is attributed to the discharge of untreated municipal wastewater to rivers as well as groundwater contamination by leaking septic tanks and pit latrines from residential areas.